Analysis of Saxophone Playing Technique and Interpretation in The Song Boha Nama Ujungna by William Nababan - Sibagariang, adi (Repertoar, 2025)
William Nababan is one of the Indonesian saxophone players involved in the music world, especially as a saxophone player who started his career in 2016. Of the many songs played by William Nababan, Boha nama ujung na is a song that has been performed by William Nababan and is the object of this research. The research aims to describe how the playing technique and interpretation are contained in this song. The data sources used in this research include interviews with sources, observation, and documentation. The research results show trill techniques, vibra, growl, outer lip techniques, diaphragm breathing, and upper end tongue. For the results of the interpretation analysis in this song, several interpretations are contained, namely, there are dynamics, such as crescendo, decrescendo, mezzo forte, forte, piano, mezzo piano dynamics. The trill, vibra, and growl techniques also produce their interpretations.